Histone lactylation-induced premature senescence contributes to 1-nitropyrene-Induced chronic obstructive pulmonary disease - Rong-Rong Wang; Dan-Lei Chen; Meng Wei; Se-Ruo Li; Peng Zhou; Jing Sun; Qi-Yuan He; Jin Yang; Hui Zhao; Lin Fu (Redox Biology)
Our previous study revealed that mice exposed to 1-nitropyrene (1-NP) develop pulmonary fibrosis and senescent alveolar cells. However, the impacts of chronic 1-NP on chronic obstructive pulmonary disease (COPD) and the underlying mechanism are unclear. Our research suggested that chronic 1-NP evoked alveolar structure damage, inflammatory cell infiltration, and pulmonary function decline in mice. Moreover, 1-NP increased p53 and p21 expression, the number of β-galactosidase-positive cells, and cell cycle arrest in mouse lungs and MLE-12 cells. Moreover, 1-NP promoted glycolysis and upregulated lactic dehydrogenase A (LDHA) and lactate production in mouse lungs and MLE-12 cells. Elevated glycolysis provoked histone lactylation, but not histone acetylation in pulmonary epithelial cells. Mechanistically, histone H3 lysine 14 lactylation (H3K14la) was upregulated in pulmonary epithelial cells. P53 knockdown mitigated 1-NP-induced cell cycle arrest and senescence in MLE-12 cells. CUT&Tag and ChIP-qPCR experiments confirmed that increased H3K14la directly upregulated p53 transcription in pulmonary epithelial cells. As expected, LDHA knockdown alleviated 1-NP-triggered cell cycle arrest and senescence in MLE-12 cells. In addition, supplementation with oxamate, an inhibitor of LDH, attenuated 1-NP-incurred premature senescence and the COPD-like phenotype in mice. These data revealed for the first time that histone lactylation-induced the increase in p53 transcription contributes to pulmonary epithelial cell senescence during 1-NP-induced COPD progression. Our results provide a basis for repressing lactate production as a promising therapeutic strategy for COPD.